2021
DOI: 10.3390/jof7050358
|View full text |Cite
|
Sign up to set email alerts
|

Daldiniaeschsone A, a Rare Tricyclic Polyketide Having a Chromone Unit Fused to a δ-Lactone and Its Symmetrical Biphenyl Dimer, Daldiniaeschsone B, from an Endophytic Fungus Daldinia eschscholtzii SDBR-CMUNKC745

Abstract: Daldiniaeschsone A (1), a rare tricyclic polyketide having a chromone unit fused to a δ-lactone and its symmetrical 6,6'-biphenyl dimer, daldiniaeschsone B (2), together with three known compounds (3-5), were isolated from a plant-derived endophytic fungus, Daldinia eschscholtzii SDBR-CMUNKC745. Their structures were elucidated by extensive 1D and 2D NMR spectroscopic data and HRESIMS. All compounds showed α-glucosidase inhibitory activity with IC50 values ranging from 0.16-0.85 mM and compound 1 was the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Meanwhile, oxindole type of alkaloids was reported in numerous studies from Penicillium sp. cultures (Hu et al, 2014;Lee et al, 2015;Xiao et al, 2018;Xu et al, 2015). In addition to our findings, previous studies on P. steckii have reported this species as a producer of mycotoxin citrinin (Yao et al, 2021), polyketides (Chen et al, 2021a), including tanzawaic acid derivatives (Malmstrùm et al, 2000), as well as isoquinoline (Yao et al, 2021) and pyrrolyl 4-quinolone alkaloids (Chen et al, 2021b).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Meanwhile, oxindole type of alkaloids was reported in numerous studies from Penicillium sp. cultures (Hu et al, 2014;Lee et al, 2015;Xiao et al, 2018;Xu et al, 2015). In addition to our findings, previous studies on P. steckii have reported this species as a producer of mycotoxin citrinin (Yao et al, 2021), polyketides (Chen et al, 2021a), including tanzawaic acid derivatives (Malmstrùm et al, 2000), as well as isoquinoline (Yao et al, 2021) and pyrrolyl 4-quinolone alkaloids (Chen et al, 2021b).…”
Section: Discussionsupporting
confidence: 77%
“…(Yurchenko et al, 2018). Nevertheless, numerous studies revealed that D. eschscholtzii is a versatile producer of polyketides with varied prospective bioactivities as antibacterial (Lin et al, 2019), cytotoxic (Wang et al, 2015), antifibrotic (Zhang et al, 2019), immunosuppressive (Zhang et al, 2011), and antidiabetic (Wutthiwong et al, 2021) agents. Therefore, in-depth chemical and pharmacological investigations of secondary metabolites from A. bunius-derived P. steckii AAB-01 and D. eschscholtzii AAB-05 are noteworthy to further study.…”
Section: Discussionmentioning
confidence: 99%
“…The endophytic fungi D. eschscholtzii is a fungus that is often encountered in tropical climates (Ng et al, 2016;Wutthiwong et al, 2021). Studies report that this fungus damages wood which is characterized by white to gray colonies and attaches to decaying wood substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Daldinia eschscholtzii is an endophytic fungus isolated commonly from mangrove plants (Yang et al, 2017 ). The diverse bioactivity metabolites, including tetralones (Liao et al, 2019a ), lactones (Kongyen et al, 2015 ), naphthoquinones (Wutthiwong et al, 2021 ), chromones (Barnes et al, 2016 ), and polyphenols (Zhang et al, 2016 ), have attracted much attention. For instance, naphthoquinones 5-hydroxy-2-methoxy-6,7-dimethyl-1,4-naphthoquinone form D. eschscholtzii HJ004 showed antibacterial activity (Liao et al, 2019b ), and chromones 5-hydroxy-8-methoxy-2-methyl-4H-chromen-4-one from D. eschscholtzii GsE13 showed phytotoxicity (Flores-Reséndiz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%